The Impact of Intellectual Property Litigation on the Stock Price of Indian Public-Listed Companies - Dey, Kushal; Huang, Jeffery (Indian Journal of Research in Capital Markets, 2024)
Purpose : Lawsuits and litigation are important components of the business landscape, as they affect a company’s financial performance and reputation. The research study explored the impact of intellectual property (IP) litigation on stock prices in India. The study utilized empirical evidence to enhance comprehension of the relationship between legal risk and financial markets. Methodology : The study used event study analysis and hypothesis testing to analyze abnormal returns (ARs) and cumulative abnormal returns (CARs) related to the filing and judgment events in intellectual property litigation. Findings : The data found conflicting reactions among plaintiffs, with considerable ARs reported in companies obtaining media coverage for their IP litigations, while those with low media attention exhibited minor variations in stock prices. However, defendants frequently experienced negative ARs following the filing of IP litigation, indicating investors’ anticipation of bad outcomes. Practical Implications : Investors can make better investing decisions by being aware of the complex relationship between legal events and stock prices. This knowledge also helps financial service providers and industry professionals deliver better services. However, given the limitations of our study, there is a need for more research, especially in the area of sector-specific analysis. Originality : In contrast to earlier research on how the market responded to legal developments, the goal of this study was to examine how IP litigation affected the company’s stock price.